In a Randomized, Placebo-Controlled Cross-Over Study, Administration of 6 and 12 G Fortetropin® Does Not Reduce Serum Myostatin in Healthy Adult Dogs Over 72-Hours - Nugent Britt, Carmella C.; Alvarez, Leilani X.; Lamb, Kenneth (Frontiers in Veterinary Science, 2021)
Objective: To evaluate the effect of a single administration of 6 and 12 g of Fortetropin compared to placebo on serum myostatin in healthy, adult dogs over a 72-h period. Methods: Prospective, placebo-controlled, randomized, double-blind, crossover study. Ten hospital-employee-owned healthy adult dogs aged 2 to 8 years old were enrolled in the study. Blood samples were collected prior to and then 12-, 24-, 36-, 48-, and 72-h following administration of the test agent (6 and 12 g) or placebo. Serum samples were processed according to manufacturer's guidelines for canine serum using GDF-8/Myostatin Quantikine ELISA kit (R&D Systems). Analysis-of-variance (ANOVA) analyses were carried out where P < 0.05 was deemed significant. Results: Mean serum myostatin was not significantly lower in treatment groups of either low or high dose compared to placebo at any time point. Baseline mean serum myostatin in low and high dose treatment groups was 29,481 (SD = 5,224) and 32,214 pg/mL (SD = 7,353), respectively. Placebo group low and high dose baseline mean serum myostatin was 30,247 (SD = 5,875) and 28,512 (SD = 5,028). Conclusion: The results of this study indicate that administration of single 6 or 12 g dose of Fortetropin does not reduce serum myostatin in healthy adult dogs over a 72-h period. Clinical Importance: Oral supplements, like Fortetropin, require further studies to determine the efficacy and bioavailability in order to guide clinical use in dogs.